On Lightly Nano w-Closed Sets - İlangovan Rajasekaran; Ochanan Nethaji (Journal of New Theory)
In this paper, we introduce and investigate the concepts of lightly nano w-closed sets and lightly nano w-open sets in a nano topological spaces, which are weaker form of lightly nano-closed sets and lightly nano-open sets and relationships among related ng-closed sets  are investigated.